2019
DOI: 10.1177/1071181319631420
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Behaviors of Physicians and Non-Physicians When Supported by an Electronic Differential Diagnosis Aid

Abstract: The present study examined a diagnostic medical decision aid developed to help inexperienced operators to diagnose and treat a simulated patient. Diagnosis and treatment accuracy using the tool were assessed and compared across both physicians and non-physicians. Initial analysis revealed more accurate diagnostic and treatment choices for non-physicians, but upon further investigation, physicians were found to have recognized signs for another diagnosis and correctly diagnosed and treated based on the limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…A study included in our review, using a poststudy questionnaire, found that doctors (pathologists) expressed higher trust in SMILY, an AI-based application, due to its better performance, interface, and higher benevolence compared with the conventional app [ 27 ]. By contrast, another study reported lower trust of experienced physicians in an AI-based recommendation tool due to its inefficient performance [ 54 ]. Based on patient data, expert physicians were able to identify the alternative and better explanation for patient health compared to the AI-based tool [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study included in our review, using a poststudy questionnaire, found that doctors (pathologists) expressed higher trust in SMILY, an AI-based application, due to its better performance, interface, and higher benevolence compared with the conventional app [ 27 ]. By contrast, another study reported lower trust of experienced physicians in an AI-based recommendation tool due to its inefficient performance [ 54 ]. Based on patient data, expert physicians were able to identify the alternative and better explanation for patient health compared to the AI-based tool [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, another study reported lower trust of experienced physicians in an AI-based recommendation tool due to its inefficient performance [ 54 ]. Based on patient data, expert physicians were able to identify the alternative and better explanation for patient health compared to the AI-based tool [ 54 ]. A recent study identified the impact of the AI interface on user’s trust [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The AI could perform better on certain tasks than others (e.g., diagnosis of different types of lesions) and the clinician would need to adjust their trust as these cases arose [25]. Further, specific environmental contexts can cause the AI to not perform well and reduce trust [8,25,33,98]. For instance, Beede et al found that poor image quality severely impacted usage of their deep learning system that made assessments based on the image of the eye [90].…”
Section: Trust Through Performancementioning
confidence: 99%